Socio-demographic correlates of age at marriage in Nepal: an empirical analysis - Sah, Nepali (Nepal Population Journal, 2018)
Age at marriage of girls is gradually increasing in Nepal, but still there is a lower age at marriage in the Terai. This paper aims to investigate the reasons for early marriage of girls among some families in Nepal with particular focus on the Terai and seeks answer to the research question ‘What are the prominent sociodemographic and cultural factors that influence marriage timing of women in Nepal?’Findings from empirical data analysis reveal that determination of marriage timing is a complex phenomenon. There are several factors that influence marriage timing of women in Nepal. Although bivariate analysis shows a further elaborative list of factors, multivariate analysis confirms the effect of each variable while controlling the effect of other variables. The prominent factors influencing marriage timing of women are age, place of birth, age at menarche, education of women and their mothers, and caste or ethnicity, and religion.The significant differences in the risk of marrying early among caste and religion groups, and the significantly higher risk among caste/ethnic groups of Terai origin and Muslims who reside mainly in the Terai, are supported by the distinct sociocultural differences with more strict marriage norms and practices prevalent among these groups. The low educational level of these groups in general and women in particular further increases their risk of marrying at an early age. An education level of some secondary and above seems to be a protective factor against early marriage, but many of the caste and ethnic groups (except Terai highcastes) and Muslims of Terai have substantially low education, particularly among women. Lower age at menarche of girls of Terai origin may also be associated with early marriage as age at menarche and age at marriage of girls were positively associated. The lower age at menarche of girls of Terai caste groups in particular seems to be an important factor creating pressure on parents to arrange marriage of their daughters at an early age.